Factors Influencing College Choice of Nepalese Undergraduate Students (Quest Journal of Management and Social Sciences, 2021)
Background: College choice decision remains one of the major issues for the students and parents especially during the time of admission.Objective: Understanding this problem, this research, taking colleges of Tribhuvan University and Kathmandu University as the samples, assesses which of the characteristics― institutional, marketing, and social are more dominant in this decision.Method: The study, based on the primary survey; uses the questionnaire to collect data among the management students of bachelor’s level in Lalitpur and Kathmandu district, shows that academic program, quality of education, and social factors are the key factors that impact college choice decision. The study employs convenient sampling techniques. The tendency of students to make college choice decisions depends on the colleges’ academic programs that they have concentrated.Result: The results suggest that college should focus their eyes to apply different types of academic programs, adopt quality education in terms of appointing highly qualified faculties and even contribute certain margin to social support, employability of the students over the market and position of enrolment of the students in higher education. These characteristics enable the colleges to run and sustain in the long run.Conclusion: To mitigate the moderating impact on college choice, the variable gender is used, however, its impact on the relationship of college fees and college choice is not supported by the study.